A Novel Synthesis of Thioglycolurils by Ring Contraction of 5,7-Dialkyl-3-thioxoperhydroimidazo[4,5-e]-1,2,4-triazin-6-ones - Gazieva, Galina A.; Poluboyarov, Pavel A.; Popov, Leonid D.; Kolotyrkina, Natalya G.; Kravchenko, Angelina N.; Makhova, Nina N. (Synthesis, 2012)
A new synthetic route to (E)-1,3-dialkyl-4-(benzylideneamino)-5-thioxohexahydroimidazo[4,5-d]imidazol-2(1H)-ones (thioglycolurils), by a ring contraction reaction of 5,7-dialkyl-3-thioxoperhydroimidazo[4,5-e]-1,2,4-triazin-6-ones with aromatic aldehydes, has been developed.
Keywords: N-heterocycles; thioglycolurils; 3-thioxoperhydroimidazo[4,5-e]-1,2,4-triazin-6-ones; aromatic aldehydes; ring contraction